2022
DOI: 10.3390/land11101717
|View full text |Cite
|
Sign up to set email alerts
|

Time Allocation and the Activity-Space-Based Segregation of Different Income Groups: A Case Study of Nanjing

Abstract: Time allocation is closely related to life quality and is a potential indicator of urban space utilization and sociospatial differentiation. However, existing time allocation studies focus on how time is allocated to various activities but pay less attention to where individuals allocate their time. In the context of China’s transformation, this study examines the differences in time allocation in different urban spaces between low- and non-low-income groups based on two methods, descriptive statistics and soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Empirical studies on residential activity spaces and living spaces have been conducted from several aspects, and the topics explored include the identification of spatial boundaries of different residential activity spaces and living spaces [125,126], evaluation of spatial quality [127][128][129], characteristics of activity spaces and living spaces [130,131], and identification of influencing factors [132,133]. Some studies analyze all of the main daily activity characteristics of residents at the spatial level [131], whilst other studies summarize the corresponding spatial characteristics from specific behaviors [134,135], and the summary of characteristics is usually combined with the analysis of influencing factors [130,136]. In terms of research data, in addition to traditional data such as in-depth interview data [137] and activity diary survey data, new types of data such as GPS data [138,139] and cell phone signaling data [140,141] have been used.…”
Section: Empirical Studies Of Residents' Activity Space and Living Spacementioning
confidence: 99%
See 1 more Smart Citation
“…Empirical studies on residential activity spaces and living spaces have been conducted from several aspects, and the topics explored include the identification of spatial boundaries of different residential activity spaces and living spaces [125,126], evaluation of spatial quality [127][128][129], characteristics of activity spaces and living spaces [130,131], and identification of influencing factors [132,133]. Some studies analyze all of the main daily activity characteristics of residents at the spatial level [131], whilst other studies summarize the corresponding spatial characteristics from specific behaviors [134,135], and the summary of characteristics is usually combined with the analysis of influencing factors [130,136]. In terms of research data, in addition to traditional data such as in-depth interview data [137] and activity diary survey data, new types of data such as GPS data [138,139] and cell phone signaling data [140,141] have been used.…”
Section: Empirical Studies Of Residents' Activity Space and Living Spacementioning
confidence: 99%
“…The characteristics of residents' activity spaces and living spaces and the factors which influence them are central research topics that have received much scholarly attention. For example, a Nanjing-specific study based on activity diary survey data found that lowincome participants who are highly dependent on the central city for their daily activities (especially work) are disadvantaged in terms of access to the central city, compared to non-low-income people who have more diverse activity spaces and can more fully utilize various types of urban areas; the factors influencing this difference include activity characteristics and the built environment, in addition to income [130]. A survey study of community residents in the Beijing Economic and Technological Development Area based on questionnaire data points out that distance, business preferences, requirements for quality of service facilities, and changes in residents' demand due to improved transportation modes, together with the spatial distribution of market supply and the relative shortage of government supply, shape the daily activity space of community residents [131].…”
Section: Urban Planning Implicationsmentioning
confidence: 99%
“…Furthermore, the socioeconomic variables are hypothesized to both directly and indirectly impact all the endogenous variables. This is because socioeconomic backgrounds affect the overall daily activity space and time allocation of individuals, which may further influence residents' neighborhood activities [40,41]. And socioeconomic variables may also explain neighborhood interaction and community ties [42][43][44].…”
Section: Introductionmentioning
confidence: 99%